2015
DOI: 10.24218/jcet.2015.07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Melanoma Stem Cells in Long-term Cultures and of SOX6 as a Specific Biomarker for these Stem Cells

Abstract: Background: Melanoma is the most aggressive skin cancer and its resistance to existing therapies in advanced stages is already known. This resistance can be directly related to the presence of cancer stem cells. We developed an experimental model that involved study of isolates of melanoma lineages (TM1 and TM5), cells that had some "stem" characteristics, in order to better characterize them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Here, we demonstrate that the intermediate state, corresponding to the transitory subset described by Tsoi et al 20 , represents a stable and distinct cell state with underlying activity of SOX6, NFATC2, EGR3, ELF1 and ETV4 GRNs (although the latter two are not specific). These TFs have previously been linked to a more aggressive/dedifferentiated phenotype in cancer and/or in melanoma specifically 32,[57][58][59] , which confirms that these cultures are in-between the melanocytic and the more deleterious mesenchymal-like state. We also determine that Hoek's cohort B cell lines and A375 display enriched activity of SOX11 and TFAP2B, and represent Tsoi's neural crest-like subgroup.…”
Section: Discussionsupporting
confidence: 62%
“…Here, we demonstrate that the intermediate state, corresponding to the transitory subset described by Tsoi et al 20 , represents a stable and distinct cell state with underlying activity of SOX6, NFATC2, EGR3, ELF1 and ETV4 GRNs (although the latter two are not specific). These TFs have previously been linked to a more aggressive/dedifferentiated phenotype in cancer and/or in melanoma specifically 32,[57][58][59] , which confirms that these cultures are in-between the melanocytic and the more deleterious mesenchymal-like state. We also determine that Hoek's cohort B cell lines and A375 display enriched activity of SOX11 and TFAP2B, and represent Tsoi's neural crest-like subgroup.…”
Section: Discussionsupporting
confidence: 62%
“…In a cancer cell line expression study, SOX6 was found to be highly expressed in melanoma cells but was not detectable in eight other cancers [86]. Additionally, SOX6 was identified as a candidate melanoma driver gene [72] in a screen and SOX6 may be a melanoma stem cell marker [51].…”
Section: Figure Andmentioning
confidence: 99%
“…Law MH 1* , Bishop DT 2* , Lee JE 3# , Brossard M 4,5# , Martin NG 6 , Moses EK 7 , Song F 8 , Barrett JH 2 , Kumar R 9 , Easton DF 10 , Pharoah PD 11 , Swerdlow AJ 12,13 , Kypreou KP 14 , Taylor JC 2 , Harland M 2 , Randerson-Moor J 2 , Akslen LA 15,16 , Andresen PA 17 , Avril MF 18 , Azizi E 19,20 , Scarrà GB 21,22 , Brown KM 23 , Dȩbniak T 24 , Duffy DL 6 , Elder DE 25 , Fang S 3 , Friedman E 20 , Galan P 26 , Ghiorzo P 21,22 , Gillanders EM 27 , Goldstein AM 23 , Gruis NA 28 35,37 , Mann GJ 38 , Molven A 16,39 , Montgomery GW 40 , Novaković S 41 , Olsson H 42,43 , Puig S 44,45 , Puig-Butille JA 44,45 , Wu W 46,47 , , Qureshi AA 48 , Radford-Smith GL 49,50,51 , van der Stoep N 52 , van Doorn R 28 , Whiteman DC 53 , Craig JE 54 , Schadendorf D 55,56 , Simms LA 47 , Burdon KP 57 , Nyholt DR 40,58 , Pooley KA 10 , Orr N 59 , Stratigos AJ 14 , Cust AE 60 , Ward SV 7 , Hayward NK 61 , Han J 46,47 , Schulze HJ…”
Section: List Of Members Of the Melanoma Meta-analysis Consortiummentioning
confidence: 99%